2018
DOI: 10.1136/medethics-2017-104695
|View full text |Cite
|
Sign up to set email alerts
|

How important is social support in determining patients’ suitability for transplantation? Results from a National Survey of Transplant Clinicians

Abstract: Social support is highly influential in listing decisions and may exacerbate transplant disparities. Providers' beliefs and reliance on social support in determining suitability vary considerably, raising concerns about transparency and justice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…On the other hand, social support and good psychological functioning of caregivers of liver transplantation patients represent a valid protective factor (Goetzinger et al, 2012; Goetzmann et al, 2012; Malik et al, 2014). As a matter of fact, social support emerged as one of the most influential factors, among transplant providers, in determining patients’ suitability for transplantation (Ladin et al, 2018). In light of that, and because of the high involvement in the patients’ care and its potential impact on patients’ long-term outcomes (Nguyen et al, 2015), the caregivers’ health should also be taken into consideration and protected.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, social support and good psychological functioning of caregivers of liver transplantation patients represent a valid protective factor (Goetzinger et al, 2012; Goetzmann et al, 2012; Malik et al, 2014). As a matter of fact, social support emerged as one of the most influential factors, among transplant providers, in determining patients’ suitability for transplantation (Ladin et al, 2018). In light of that, and because of the high involvement in the patients’ care and its potential impact on patients’ long-term outcomes (Nguyen et al, 2015), the caregivers’ health should also be taken into consideration and protected.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Yeates et al have shown that the wait times are longer for Indigenous vs all other (living and deceased) transplant recipients in Australia (2.4 vs 1.5 years), Canada (2.1 vs 1.5 years), New Zealand (2.2 vs 1.2 years), and the United States (2.1 vs 1.1 years). Delayed referral for transplant evaluation by a nephrologist is a possible explanation for this discrepancy, an explanation that is associated with higher mortality, longer time on the waitlist, and decreased likelihood of receiving a transplant . Another possible explanation is that nephrologists are more likely to identify Indigenous patients as non‐adherent with dialysis and high‐risk transplantation candidates .…”
Section: Discussionmentioning
confidence: 99%
“…While not researched extensively, it is possible that poor social support networks may also impact postoperative outcomes. The adverse effects of longer wait times are well known and have been shown to impact a patient's psychological well‐being in a negative manner . Graft survival rates are considerably worse among patients on dialysis for more than 24 months when compared to those on dialysis for less than six months for patients who receive kidneys from both deceased (39% vs 69% survival rate, respectively) and living (49% vs 75% survival rate, respectively) donors at 10 years post‐transplant .…”
Section: Discussionmentioning
confidence: 99%
“…Prior findings suggest that social support is one of the most important factors considered in transplant listing decisions, but what constitutes adequate social support is poorly understood. 8,9 Compared to physicians and surgeons, psychosocial clinicians were twice as likely to rely upon social support in listing decisions. 5 While transplant teams commonly rely on psychosocial clinicians to determine patients’ psychosocial eligibility for transplantation, questions remain about how these clinicians evaluate social support.…”
Section: Introductionmentioning
confidence: 99%